From unfair prices to unfair trading practices: Political economy, value chains and 21st century agri-food policy - Swinnen, Johan; Olper, Alessandro; Vandevelde, Senne (International Association of Agricultural Economists, 2021)
This article analyzes how value chains play a role in the political economy of agricultural and food policy by (1) discussing historical insights; (2) reviewing an emerging literature on political economy of trade policy and value chains and drawing implications for agricultural and food policy; (3) discussing market power issues with increasing concentration in agri‐food value chains and its implications for government regulations; and (4) presenting a political economy case study of recent regulations that have explicitly targeted value chain structures in the agri‐food sector: the EU regulations on “unfair trading practices (UTPs)”. The case study is of wider relevance since it addresses a key concern in global value chains.